Seizure Following Topical Gammabenzene Hexachloride Therapy - Biswas Animesh; Chakraborty Swapna; Datta Pijush Kanti (Wolters Kluwer Medknow Publications, 2002)
Development of short-lived, self-limiting major epileptic seizures following an improper application of gammabenzene hexachloride (GBHC) lotion in a 15 month old boy suffering from scabies with secondary bacterial infection is reported here due to its rarity in clinical practice and, more particularly, to stress the need of correct instructions on the use of GBHC application for the prevention of iatrogenic neurotoxicity.